Synthesis and Characterization of Zeolite Membrane - Hens Saputra; Moch. Rosjidi (Institut Teknologi Bandung, 2004)
The zeolite membrane of MFI could be sinthesized on alpha alumina support having an asymmetric structure and a pore diameter of top layer being about 0.1 Î¼m. In this experiment, the method performed was a hydrothermal process being done at temperature 303 K by using Silica colloidal with the the composition of 30% SiO2, 0.04% Al2O3, 0.4% Na2O and NaOH 4N. The membranes produced were characterized by scanning electron microscope (SEM), X-ray diffraction (XRD), X-ray diffraction (XRD), Energy Dispersive X-ray Spectrofotometer (EDX) and gas permeation, which use some pure gases such as carbon dioksida, methane, n-butane and ibutane. Based on the SEM observation, the top layer of MFI zeolite membrane produced was about 20 Î¼m. The Analysis and mapping by using EDX showed that the zeolite membane was formed on top and inside of the support. Based on the gas permeation test, the permeance of nitrogen increased while the temperature encreased, and the result showed that the permeance ratio of n-butane/i-butane was about 60. Meanwhile, the selectivity of n-butane/i-butane at 300 K was 62. The simulation test of gas separation was performed by applying the mixture of nbutane and i-butane as a model and the temperature variation of 300 K, 340 K and 380 K. In this case, the Test used a pervaporation methode in which helium as inert gas (i.e. sweep gas) and on line analysis by using gas chromatography. The Flux of gas being through the membrane was measured by flow meter. The Selectivity of the mixture of n-butane and i-butane at temperature 300 K obtained was 62, and its selectivity decreased while the temperature increased.